KONSEP TA'DIB SYED NAQUIB AL-ATTAS SEBAGAI PENGUATAN ETIKA DIGITAL DALAM PENDIDIKAN ISLAM KONTEMPORER - Ana Fika, Biaunika; Hushunul Ahadiyah, Fina; Supriyatno, Triyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of digital technology has had a significant impact on education, including the emergence of ethical challenges and moral degradation among the younger generation. The high intensity of internet use requires a strong ethical foundation so that students are able to interact wisely in the digital space. This study aims to examine the concept of ta'dib according to Syed Naquib Al-Attas and analyze the implementation of the concept of ta'dib as a reinforcement of digital ethics in contemporary Islamic education. The research method used is library research by examining Al-Attas's main work “The Concept of Education in Islam” and various supporting literature related to ta'dib and digital ethics. Data analysis was conducted through a content analysis approach. The results show that the concept of ta'dib, which emphasizes the cultivation of manners as the core of education, has strong relevance in shaping ethical behavior in the digital space. Ta'dib values such as honesty, responsibility, moral discipline, the proper use of knowledge, and respect for fellow digital users are in line with the principles of digital ethics that are needed today. Thus, ta'dib can be a philosophical and pedagogical foundation for strengthening digital ethics, so that Islamic education can produce a generation that is intelligent, civilized, and wise in the use of technology.